Combined heating operation optimization of the novel cogeneration system with multi turbine units. (1st September 2018) - Li, Wentao; Tian, Xiaofeng; Li, Yan; Ma, Yifeng; Fu, Lin
Highlights: A new type of connecting and switching method for the cold end system is proposed. Method of equivalent electricity of heating is used to analyze energy consumptions. Combined heating strategy optimization for the multi turbine units is analyzed. Heating performances and energy consumptions of the novel system are analyzed. The novel cogeneration system drops the heating energy consumption by 47.7%. Abstract: At present, large extraction condensing turbine units are generally adopted for combined heating in the cogeneration plants of northern China. A large amount of condensed waste heat of the exhaust steam releasing to the environment leads to a great heat loss of the cold end system. The novel cogeneration system significantly improves energy efficiency of the plant by efficiently recovering the condensed waste heat of multi turbine units. For the turbine units with complete recovery of the condensed waste heat, the corresponding cooling towers are closed during the freezing period. With the reduction of the heat load, the surplus condensed waste heat should be discharged by the cooling towers. However, the outdoor wet-bulb temperature is very low during the severe cold period, which results in a surplus of the cooling capacity of the cooling towers. When releasing a small amount of the condensed waste heat, the cooling towers may confront with the frozen risk. A new type of connecting and switching method for the cold end system of the multi turbine units is proposed to avoid the frozen risk. On this basis, with the method of equivalent electricity of heating, an optimized combined heating operation strategy is proposed for the multi turbine units under full operating conditions. The case study takes 4 × 300 MW turbine units as an example, the heat load regulation process is simulated according to the optimized strategy and the discussions are made on the seven regulation stages. Furthermore, the heating performance of the absorption heat pumps and the variation and distribution regularities of the energy consumptions during the heating period are analyzed in detail. Case study results show that, the heating coefficient of performance of the absorption heat pumps is obviously improved after the steam-water heat exchanger withdraws from heating. Compared with the traditional cogeneration heating system, the novel cogeneration system reduces heating energy consumption by 47.7% under the premise of avoiding the frozen risk of the cooling towers during the winter.